Larangan Kepemilikan Tanah Pertanian Secara Absentee Dan Pertanggung Jawaban Hukum Badan Pertanahan Di Kabupaten Tulungagung - Nugraha, I Wayan Putra; Ari Atu Dewi, Anak Agung Istri (Acta Comitas : Jurnal Hukum Kenotariatan, 2020)
Reforms have been carried out by the government through many land reform programs that regulate land ownership and legal relations between owners and land objects, so that a prosperous and productive society is created to advance the national economy and food security. One of them is the prohibition of agricultural land ownership regulated in article 10 paragraph (1) of the Basic Agrarian Law. It is expected that the owners of agricultural land will work on their own land so that productivity will be maximized, the community will be taught to work and be productive regularly and routinely. But in reality in the field in Jabalsari village Sumbergempol subdistrict Tulungagung regency there are still many people who control agricultural land absentee and interpreted the rules of ownership of agricultural land absentee not yet effective, so this research aims to find out the causes of absentee ownership of agricultural land and how a large role Tulungagung Regency National Land Agency in terms of absentee ownership of agricultural land. This research is carried out using the Empirical Juridical method namely how the law is implemented in social life. The results of research conducted in Jabalsari village Sumbergempol Sub-district Tulungagung District showed that absentee land ownership in Tulungagung District occurred due to many factors namely: community awareness factors, cultural factors, legal factors, law enforcement factors in the area, facility and infrastructure factors as well as quite a lot It was found that economic factors, and the responsibility of the National Land Agency of Tulungagung Regency still reached the supervision of certified land and improved administration of agricultural land data, this was done so that in the future it would run and orderly administration of the problem of absentee ownership of agricultural land.